Inkonsistensi Pengaturan Cuti Kampanye Calon Presiden: Analisis Pasca Amandemen UUD 1945 dan Saddu Dzariah - Afrinal; Supardi; Faisal Efendi; Ikhwanuddin Abdul Majid; Nimuhammadfatin Samae (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
Indonesian constitutional practices, the office of president has undergone many major changes since the amendment of the 1945 Constitution. Some of these changes include the direct election of the president and vice president by the people and restrictions on the president's term of office. It is very beneficial that the president is elected directly by the people. This also shows that Indonesia uses a presidential and republican system of government. The focus of this study is the regulation of presidential candidates' leave from work from a legal and Saddu Dzariah perspective. This study uses qualitative methods uses library research by using the normative juridical method. The literature studied in the Law, Government Regulations, books, journals. The method used is normative juridical The main data was obtained through regulations related to this article. The Presidential elections of the reform era have undergone three significant changes, differing rules regarding the candidates' leave. including the obligation to take leave on holidays and not take leave on holidays. The difference in the Presidential elections of 2004 and 2009 was that the incumbent candidates took campaign leave, including holidays, whereas in the 2019 election, there was none. The similarity among the incumbent candidates: all three did not limit the campaign leave time for the candidates. When viewed from the perspective of Saddu Dzariah ensures that justice is applied correctly, avoiding damage. there are also concerns about influencing the state institutions below it, pressuring someone to vote for the incumbent President, disadvantaging other Presidential candidates.